Strategi Pengembangan Usaha Wedding Organizer Arunika di Kota Padang - Febrian Rafqi Akbar; Hijriyantomi Suyuthie (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to identify internal and external factors influencing the development of the Arunika Wedding Organizer business in Padang City and formulate appropriate strategies through a SWOT analysis approach. The research method was conducted qualitatively, with data collection techniques through in-depth interviews with five informants, consisting of business owners, employees, and vendors who collaborate with Arunika. The data obtained was then analyzed to map the strengths, weaknesses, opportunities, and threats faced by the company. The results show that the main strengths of Arunika Wedding Organizer lie in responsive service to client needs, solid team coordination, and good working relationships with supporting vendors. These factors are important capital in maintaining consumer trust. However, the study also found weaknesses such as a limited number of part-time teams that can hinder operational flexibility, and suboptimal digital promotions that limit market reach. From the external side, opportunities that can be utilized include the increasing trend of more personal and simple intimate weddings, and the high demand for one-stop services, where all wedding needs can be accommodated by a single service provider. Meanwhile, the threats faced stem from intense price competition with similar service providers and relatively rapid changes in wedding trends, requiring the company to be constantly adaptive. Based on the SWOT matrix analysis, Arunika Wedding Organizer falls into quadrant IV (hold and maintain). Therefore, the recommended strategy is to maintain existing strengths while addressing existing weaknesses, particularly in human resources and digital promotion.